2021
DOI: 10.1101/2021.01.04.425279
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Medium-throughput zebrafish optogenetic platform identifies deficits in subsequent neural activity following brief early exposure to cannabidiol and Δ-9-tetrahydrocannabinol

Abstract: In the light of legislative changes and the wide spread use of cannabis as a recreational and medicinal drug, delayed effects of cannabis upon brief exposure during embryonic development are of high interest as early pregnancies often go undetected. Here, zebrafish larvae were exposed to cannabidiol (CBD) and Δ-9-tetrahydrocannabinol (THC) until the end of gastrulation (1-10 hours post-fertilization) and analyzed later in development (4-5 days post-fertilization). In order to measure neural activity, we implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…In comparison, there is less evidence of a role for CB2 in neurodevelopment. Recent studies in zebrafish showed that blocking CB2 with pharmacological tools in early development altered motor neuron growth [71] and that the early effects of THC and CBD exposure on neural activity can be partially prevented by CB2 antagonists [72].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, there is less evidence of a role for CB2 in neurodevelopment. Recent studies in zebrafish showed that blocking CB2 with pharmacological tools in early development altered motor neuron growth [71] and that the early effects of THC and CBD exposure on neural activity can be partially prevented by CB2 antagonists [72].…”
Section: Discussionmentioning
confidence: 99%
“…We document that CBD has direct neuroteratogenic effects on progression of both cranial and spinal NT closure in mice. Effects of CBD on neuron function and behavior have previously been studied in zebrafish (Carty et al, 2018; Carty et al, 2019; Kanyo et al, 2021), but this species does not close its NT in the same way as mammals do. The mechanisms by which CBD impairs the progression of NT closure have not been identified here and their delineation is likely to require substantial future work.…”
Section: Discussionmentioning
confidence: 99%
“…12 Thus, the adverse effects noted with THC products may still apply, and there is some suggestion of a synergistic effect between THC and CBD in animal models. 13 Development of urine and serum assays to help ascertain use of CBD products will be helpful in moving the field forward, given the inability to rely on selfreported use in pregnancy because of the drastic underestimation of use in self-reported data. 14,15 This publication in Obstetrics & Gynecology represents an important initial step in investigating the use of CBD-only products in pregnancy.…”
Section: Financial Disclosurementioning
confidence: 99%